Investigation of compact dual port octagonal MIMO antenna with triple band rejection capabilities with good isolation - et. al., H. Sudarsan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This papers focuses to investigate a 35mm*60mm*1.6mm novel dual port MIMO antenna with triple notch rejection capabilities that exhibits good isolation performances. An Octagonal radiating patch is incorporated with defected ground structure and relevant slots in the radiator. Two slots and DGS contribute for the rejection capabilities of potential interference bands like WIMAX,WILAN, and X band in the ultra-wide band region of the designed antenna. Further to improve its performance, the antenna is modified as dual port MIMO which experiences mutual coupling. A strip line is introduced above the radiating patches in the substrate to obstruct the surface waves and to reduce the mutual coupling between the radiating elements. Crucial parameters like mutual coupling and the diversity gain are analyzed and are found to be promising. The proposed variant’s impedance bandwidth spans from 1.5 GHz to 9.05 GHz.